TINDAKAN PENGEPUNGAN YANG MENYEBABKAN KELAPARAN DI MADAYA DALAM PERSPEKTIF HUKUM HUMANITER INTERNASIONAL: THE SIEGE CAUSING STARVATION IN MADAYA FROM AN INTERNATIONAL HUMANITARIAN LAW PERSPECTIVE - Zulfa, Aninda Aulia; Patrecia, Audrey Putri; Uli, Cena Lucia; Justinar, Jun (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2022)
The Syrian people's rebellion against their government was a form of disappointment with the Al-Assad Regime, a conflict that triggered many victims and losses. The conflict between the rebels and the Syrian government resulted in violations of Geneva Law and Hague Law. The Syrian war spread to Damascus, the capital of Syria. As a result, the city experienced some of the effects of fighting between the rebellion and the Syrian government. One of the areas affected is Madaya, which is near Damascus. The city of Madaya is under siege by the Syrian government so around 40 thousand civilians there experience a crisis of basic needs such as clean water, medicine, and food, which triggers hunger and causes many victims. In addition, the use of landmines in the Syrian war is a crime that violates humanitarian law and requires the Syrian government to take full responsibility for the material and immaterial losses resulting from the threat of siege and the use of beatings. Therefore, a view of international humanitarian law is needed in the Syrian war.